The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.5334/gh.1138
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practice Toward Cardiovascular Diseases in the Lebanese Population

Abstract: Background & Objective: Cardiovascular diseases (CVD) are the leading cause of death globally. Assessing CVD knowledge, attitude, and practice (KAP) is necessary to spread awareness about CVD in Lebanon, their corresponding risk factors, and behaviors in which individuals can avoid or minimize the possibility of developing a CVD. Subjects & Methods: This was a case-control analytical study that targeted 921 CVD and non-CVD subjects. A questionnaire form was used to coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Regarding physical activity per week, it was also at a moderate level. When we examined each subgroup separately, we found that the average knowledge score related to CVD in CVD patients was lower than non-CVD responders, unlike the Machaalani et al study in which CVD patients showed more knowledge about CVD than non-CVD responders [ 12 ]. However, as was also noticed in other studies, the degree of knowledge in both sub-populations remained low.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Regarding physical activity per week, it was also at a moderate level. When we examined each subgroup separately, we found that the average knowledge score related to CVD in CVD patients was lower than non-CVD responders, unlike the Machaalani et al study in which CVD patients showed more knowledge about CVD than non-CVD responders [ 12 ]. However, as was also noticed in other studies, the degree of knowledge in both sub-populations remained low.…”
Section: Discussionmentioning
confidence: 70%
“…Among the whole population in our study, 88.5% correctly acknowledged the relationship between CVD and the heart, while 84.4% understood that hypertension is a CVD risk factor. Likewise, other studies demonstrated that patients were mostly aware of smoking, diabetes, and hypertension as risk factors for CVD [ 10 , 12 ]. However, in our study, 57.7% believe that most cancer is not a CVD risk factor, and 69.4% incorrectly think that cardiovascular disease is not the primary cause of death in diabetic patients.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Therefore, increasing education and awareness is critical. Machaalani et al, (2022) reported that the knowledge and practices regarding cardiovascular diseases were undesirable and recommended well-structured national awareness events to be carried out. Physiological factors are one of the most common causes of palpitations (Alanzi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%